2000
DOI: 10.1093/brain/123.12.2512
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and hemispheric language dominance in healthy humans

Abstract: In most people the left hemisphere of the brain is dominant for language. Because of the increased incidence of atypical right-hemispheric language in left-handed neurological patients, a systematic association between handedness and dominance has long been suspected. To clarify the relationship between handedness and language dominance in healthy subjects, we measured lateralization directly by functional transcranial Doppler sonography in 326 healthy individuals using a word-generation task. The incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
796
1
31

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,338 publications
(890 citation statements)
references
References 29 publications
62
796
1
31
Order By: Relevance
“…However, similar to [14], we did not find sex differences in speech laterality. If digit ratio is a reliable surrogate for pT the lack of a sex effect in speech representation would appear to be a challenge for androgen accounts of cerebral lateralisation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, similar to [14], we did not find sex differences in speech laterality. If digit ratio is a reliable surrogate for pT the lack of a sex effect in speech representation would appear to be a challenge for androgen accounts of cerebral lateralisation.…”
Section: Discussionsupporting
confidence: 57%
“…A limitation of this approach is that handedness does not correlate perfectly to speech laterality. Although it is well known that for most humans the left-hemisphere is dominant for speech and handedness, some right-handers, and many ambilaterals and lefthanders have bilateral or right-hemisphere representation [14]. Moreover, handedness is multidimensional and there is no clear consensus on the precise components of handedness that may be related to speech representation.…”
Section: Q2mentioning
confidence: 99%
“…Then, a subset of the participants took part in an fMRI based validation study. This study comprised the assessment of hemispheric dominance for language production, in a set-up employing a mental word generation task known to produce marked lateralization, in both fMRI and fTCD settings, which is in agreement with the lateralization determined by a Wada test (Knecht et al, 2000(Knecht et al, , 2001(Knecht et al, , 2003.…”
Section: Methodsmentioning
confidence: 78%
“…Knecht et al (2000) observed that in a student population up to 25% of strong left-handers have bilateral or right hemisphere dominant representation of their speech production, against a mere 5% of strong right-handers. It was a vital component of our study to be able to compare behavioral performance differences ranging from RVF advantage to LVF advantage with expected LH to RH dominance patterns obtained in the scanner.…”
mentioning
confidence: 97%
“…Our sample only comprised individuals presenting with symptoms. Broca's and Wernicke's speech areas are located in the left hemisphere for about 95% of right handers, but about 70% of left handers (Knecht et al., 2000). It is possible that the stroke could be less noticeable in the right hemisphere perhaps as the speech is less likely to be affected, thus indicating that maybe a percentage of RSSI that occur in the right hemisphere is disregarded and, therefore, unreported.…”
Section: Discussionmentioning
confidence: 99%